Shariah parameters for musharakah contract: A comment - Che Arshad, Noraziah; Ismail, Abdul Ghafar (Centre for Promoting Ideas, 2010)
Bank Negara Malaysia (BNM), the central bank, has already published the draft of its latest Shariah parameter on Musharakah contract. The general aim of which are to provide a standard guidance on applying respective Shariah contracts in Islamic finance and also to promote the harmonization of Islamic finance market practices in Malaysia. The essential features attributable to a Musharakah contract, according to the draft will serve as guidance for Musharakah transactions and to ensure Musharakah business activities and innovations are within their risk management capacity and do not compromise the long-term sustainability of the business. The guidelines also aim to promote operational efficiency and best practices that would safeguard the interests of stakeholders and in particular participants. In this paper we provide the discussion how : i) the features identified in this parameter will serve to assist the Islamic jinancial services industry to identify, understand, apply and distinguish the contract from other contracts prevalent in the industry; ii) the features identified and described in this parameter are extracted from the text of fatwas opined. What do we expect from this paper may identify if a special rules apply to a types of contract musharakah especially in musharakah al-milk and musharakah al-aqd because their implication on conflict of interest.